How Was the War Communicated? Comparative Analysis of The Satirical Press During the War Against Paraguay and The War of The Pacific - Sosa Vota, Silvina (Revista de Historia Social y de las Mentalidades, 2023)
During the second half of the 19th century, two crucial military conflicts occurred between South American states: the War against Paraguay and the War of the Pacific. During these processes, the satirical press, characterised by the inclusion of humorous images, generated discourses and narratives of the events to inform urban societies, distant from the development of the events, what was happening and who the different actors involved were. This paper will seek to analyse how satirical newspapers in Rio de Janeiro and Santiago de Chile developed this work in the active moments of the conflict from a comparative and cultural perspective.
Keywords: Caricatures; Newspapers; War of the Triple Alliance; War of the Pacific